Pengaruh Digital Marketing, Harga, Kualitas Produk, Dengan Kepuasan Sebagai Moderasi Keputusan Pembelian Pada Fore Coffe Di Balikpapan - Marsianto, Nikolas Heru; Saputra, Dodi; Andrianto, Farista Cahya; Benu, Andika; Hasan, Syahril (Lembaga Teewan Journal Solutions, 2026)
This study examines the effects of digital marketing, price, and product quality on purchasing decisions at Fore Coffee in Balikpapan, with customer satisfaction acting as a moderating variable. The rapid growth of the modern coffee industry has encouraged businesses to adopt effective digital marketing strategies, competitive pricing, and consistent product quality to influence consumer purchasing behavior. A quantitative survey was conducted involving 200 Fore Coffee consumers selected through purposive sampling. Respondents were required to have purchased Fore Coffee products at least twice within the last six months. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that digital marketing, price, and product quality positively and significantly influence purchasing decisions. Product quality emerged as the most influential factor among the independent variables. Furthermore, customer satisfaction significantly strengthens the relationships between digital marketing, price, product quality, and purchasing decisions. These results indicate that satisfied consumers are more responsive to marketing efforts, perceive prices more positively, and are more likely to make purchasing decisions when product quality meets their expectations. The study provides practical insights for Fore Coffee to enhance its digital marketing strategies, maintain product quality, and implement pricing policies that support customer satisfaction and purchasing decisions.